2023
DOI: 10.1371/journal.pone.0280237
|View full text |Cite
|
Sign up to set email alerts
|

Will R&D make investors more tolerant? Analysis based on the performance forecast of Chinese listed companies

Abstract: In the era of innovation dividends, whether investors, as the main participants in the capital market, can tolerate enterprise innovation activities is the key to whether the capital market can help enterprises innovate. This paper takes the listed companies of Shanghai and Shenzhen A-shares in China that disclosed quantitative performance forecasts from 2016 to 2021 as samples, obtains the market reaction of performance forecasts through the event study method and uses them as proxy variables of investors’ sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that diatomite modification can increase the viscosity and shear modulus of asphalt binder, leading to better rutting resistance of asphalt mixtures [8,9]. The absorption of asphalt into the porous structure of diatomite increases the stiffness of the asphalt mortar, which enhances the resistance to permanent deformation [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that diatomite modification can increase the viscosity and shear modulus of asphalt binder, leading to better rutting resistance of asphalt mixtures [8,9]. The absorption of asphalt into the porous structure of diatomite increases the stiffness of the asphalt mortar, which enhances the resistance to permanent deformation [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Diatomite can be directly added into the asphalt mixture without pre-treatment or special equipment [20]. The interaction between diatomite and asphalt binder is mainly physical rather than chemical, through mechanisms such as absorption, adsorption and mechanical interlocking [9].…”
Section: Introductionmentioning
confidence: 99%
“…This can have a big impact on business-to-business (B2B) relationships by enhancing customer experience (CRM) and adding value for all stakeholders [1]. The health industry is only one of the many industries that have been significantly impacted by the rapid advancements in digital technology [2]. Digital transformation (DT) has gained recognition as a key tactic for enhancing hospital performance (HP) in recent years, with an emphasis on enhancing overall health services, patient care quality, and operational efficiency.…”
Section: Introductionmentioning
confidence: 99%